2011
DOI: 10.1007/s11270-011-0767-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Remediation of Pentachlorophenol Contaminated Clay Soil

Abstract: This paper presents a bench-scale experimental study performed to investigate the remediation of low permeable soil contaminated with pentachlorophenol (PCP) using the electrokinetic technique. A total of six electrokinetic tests were performed using kaolin soil spiked with 100 mg/kg of PCP. The first three tests were performed with an applied voltage gradient of 1 VDC/cm, where each test employed one of the three different flushing solutions: deionized water, electrolyte, or buffered electrolyte. The other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…. ) was critical to maintain a high electroosmotic flow and achieved a satisfactory removal [24,27,28]. Furthermore, the interaction of surfactants with soil may clearly reduce the effectiveness of the electrokinetic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…. ) was critical to maintain a high electroosmotic flow and achieved a satisfactory removal [24,27,28]. Furthermore, the interaction of surfactants with soil may clearly reduce the effectiveness of the electrokinetic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Electrokinetic remediation is an effective technology for the remediation of organic contaminated soil (Alcántara et al, 2008(Alcántara et al, , 2012Pazos et al, 2010;Reddy et al, 2011). Electrochemical oxidation, an important component process of electrokinetic remediation, has been suggested as an effective pathway to remove organic pollutants from soil (Rahner et al, 2002;Andreottola and Ferrarese, 2008;Istrate et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Periodic voltage application consists of a cycle of continuous voltage application followed by a period of "down time" where the voltage was not applied was found to allow time for the mass transfer, or the diffusion of the contaminant from the soil matrix, to occur and also polarize the soil particles. Several laboratory studies have demonstrated such desirable electro-osmotic flow behavior in a consistent manner, but field demonstration projects are needed to validate these results under scale-up field conditions [29,30]. …”
Section: Removal Of Organic Contaminants By Electrokinetics: Limitatimentioning
confidence: 99%